Analisis Pengaruh Upah Minimum, Pertumbuhan Ekonomi, Jumlah Penduduk dan Inflasi Terhadap Ketimpangan Pendapatan Provinsi di Pulau Sumatera - Razi Rahman; Dewi Zaini Putri (Universitas Negeri Padang, 2021)
This study aims to examine the effect of Minimum Wage, Economic Growth, Population and Inflation on Income Inequality of Provinces in Sumatra Island. This type of research is descriptive, the data used are secondary data and panel data from 2013 to 2020 in 10 provinces on the island of Sumatra. Using panel regression analysis method with Random Effect Model method. The results of the study concluded that the minimum wage variable had a significant negative effect on income inequality, while economic growth, population and inflation had a positive and negligible effect on income inequality. Based on the findings in this study, the policy that can be suggested by the government is to distribute income in each region in order to reduce inequality between regions.